Commentary on Schotanus, "Singing and Accompaniment Support the Processing of Song Lyrics and Change the Lyrics' Meaning" - Lee, Christopher S. (Empirical Musicology Review, 2020)
In this commentary, a number of problematic aspects of the studies presented in the target article are discussed. Suggestions have been made for further analyses of some of the data and for additional experimental investigations.